Penerapan Terapi Nebulizer Terhadap Peningkatan Saturasi Oksigen Pada Pasien Dyspnea Melalui Aplikasi Teori Virginia Henderson Di Rsud Dr M.Yunus Bengkulu Tahun 2025 - Zantika, Ninalia; Murwati, Murwati (Jurnal Kesehatan Mitra Sekawan, 2026)
Dyspnea is a common symptom experienced by patients with respiratory disorders such as bronchopneumonia. The decrease in oxygen saturation due to dyspnea can interfere with the basic need to breathe normally. This study aims to determine the effect of nebulizer therapy on improving oxygen saturation in patients with dyspnea through the application of Virginia Henderson’s theory. The study employed a descriptive design with a case study approach involving two pediatric patients aged 7 and 8 years at Dr. M. Yunus General Hospital, Bengkulu. The intervention provided was nebulizer therapy administered three times a day for two consecutive days. After the nebulizer therapy was given, the results showed an increase in oxygen saturation from 90% to 96% in the first patient and from 91% to 97% in the second patient. These findings indicate that nebulizer therapy is effective in increasing oxygen saturation and in fulfilling the basic need for breathing as described in Virginia Henderson’s theory. This theory-based nursing approach has been shown to make a positive contribution to nursing care for patients with respiratory disorders.